Sistem Pendukung Keputusan Menentukan Kinerja Aparatur Kecamatan Di Kantor Camat Galang Dengan Menggunakan Metode AHP - Sri Wahyu Ningsih; Sulindawaty (Jurnal Ilmu Komputer dan Sistem Informasi (JIKOMSI), 2020)
The State Civil Apparatus is always required to have full loyalty and obedience in carrying out its duties. Decision support systems can be used as a solution to a problem or for an opportunity. AHP method is a method that can help solve complex problems by structuring a hierarchy of criteria. Based on this research, the researcher tries to prove the previous research and improve the accuracy of the data so that the researcher takes the title "Decision support system determines the performance of the sub-district apparatus in the Galang sub-district office using the AHP method. It is intended that the new information generated can increase knowledge about determining the performance of sub-district officials at the Galang sub-district office.